CLASSIFICATION OF EASTERN EUROPE COUNTRIES ABOUT SIMILARITIES OF TRAINING OF EXPERTS IN THE FIELD OF EDUCATION - Tryhub, I. (Continuing Professional Education: Theory and Practice, 2019)
The article explores the different approaches to the classification of countries in Eastern Europe and analyzes the experience of training of experts in the field of education in such Eastern European countries as Poland, Hungary, Czech Republic, Slovakia, Slovenia, Bulgaria, Romania, Lithuania, Latvia, Estonia and Russia. Analysis of training of experts in the field of education in Eastern European countries performed on the following of criteria’s: availability of specialized accreditation agency; development of tools and methodologies for assessing quality; checking the quality of education; procedure for selection of experts; forms of training experts; periodic publication of reports of agencies. Thus, the experience of training of experts in the field of education in Eastern Europe coincides the majority of defined criteria’s of similarities. The differences is founds in the selection procedure and forms of training of experts in the field of education. Thus, in the Slavic countries of EU agencies do not prepare experts in the field of education. They can choose according to their educational experience. Only Slovenia keeps a register of experts and conducts periodic trainings and conferences for them. In the Baltic countries, the role of experts in the field of educational perform leading domestic and foreign teachers, which gives briefings and training form of studying. In the Balkan countries, experts is chosen among experienced professionals whose training is not provides. Russia are preparing consultants of education and accreditation experts within postgraduate education, using such forms of work, such as: seminars, round tables, training courses, postgraduate degrees. The main control procedures of quality of education in Eastern European countries are the licensing, certification and accreditation.